2001
DOI: 10.1046/j.1537-2995.2001.41040504.x
|View full text |Cite
|
Sign up to set email alerts
|

Human platelets express gangliosides with LKEactivity and ABH blood group activity

Abstract: In addition to sialyl-iI and sialyl-Le(x) gangliosides, group A platelets express gangliosides with LKE activity and group A activity. Like RBCs, group A-active gangliosides may act as alloantigens and autoantigens to naturally occurring isohemagglutinins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 68 publications
(138 reference statements)
1
28
0
Order By: Relevance
“…Badros et al 16 also showed that major/ bidirectional ABO incompatibility led to delayed platelet engraftment and an increased requirement for platelet transfusion in patients who underwent PBSCT using a nonmyeloablative conditioning regimen. Although ABH antigens are also expressed on platelets, 17,18 most of the previous studies did not show an association between major/bidirectional ABO incompatibility and delayed platelet engraftment or increased platelet transfusion requirement after SCT. The reason for the delayed platelet engraftment in major/bidirectional ABO-incompatible CBT could not be clearly explained.…”
Section: Discussionmentioning
confidence: 95%
“…Badros et al 16 also showed that major/ bidirectional ABO incompatibility led to delayed platelet engraftment and an increased requirement for platelet transfusion in patients who underwent PBSCT using a nonmyeloablative conditioning regimen. Although ABH antigens are also expressed on platelets, 17,18 most of the previous studies did not show an association between major/bidirectional ABO incompatibility and delayed platelet engraftment or increased platelet transfusion requirement after SCT. The reason for the delayed platelet engraftment in major/bidirectional ABO-incompatible CBT could not be clearly explained.…”
Section: Discussionmentioning
confidence: 95%
“…GSLs were detected by chemical staining with diphenylamine reagent or by HPTLCimmunostaining with blood group-specific MoAbs as described. 3,25 All samples were immunostained in duplicate. All samples staining negative for either A, B, or Lewis antigens were repeated at twice the initial GSL concentration.…”
Section: Neutral Gsl Isolation and Analysismentioning
confidence: 99%
“…Membranes were immunostained for GPIIb (CD41b, AMAC, Westbrook, ME) and ABH using the ABC streptavidin system (Vector Laboratories) described for HPTLC-immunostaining. 3,24,25 Gels were retained and stained with Coomassie Brilliant Blue. All Western blot-negative samples were repeated at 80 g/well.…”
Section: Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis (Smentioning
confidence: 99%
See 2 more Smart Citations